Effectiveness of Cognitive Behavior Therapy (CBT) Group Counseling to Increase Self-Determination in Middle School Students - Renata Noor Inayah Oetomo,; Cindy, Pravesti (Edu Consilium : Jurnal Bimbingan dan Konseling Pendidikan Islam, 2025)
Self-determination is an important factor in living life. The cause of low self-determination is the dominance of negative thoughts. Self-determination can be increased through various efforts or endeavors, one of which is fighting negative thoughts through cognitive behavior therapy counseling. The aim or purpose of this research is to increase self-determination through cognitive behavior therapy group counseling activities. Quantitative research takes the form of a pre-experimental one group pre-test post-test design which takes samples using a simple random sampling technique so that it becomes a reference in this research method. The application of the instrument or implementation of the instrument in this research is by using a self-determination scale which has been tested for validity and reliability. From the research that has been carried out, it is stated that the results of the implementation of cognitive behavior therapy group counseling are effective in increasing the self-determination of class VIII students at SMP PGRI 1 Buduran Sidoarjo, with the results of statistical tests calculated by the Wilcoxon test having a significance value (2-tailed), namely 0.042 < 0.05.